Speech acts in Chris Rock’s Stand-Up Comedy Show "Selective outrage" - Humaniika, Eko Setyo; Dewi, Septi Riana; Matas, Gordan; Radjaban, Yohanes; Rizki, Akbar Arif (Journal of English Language and Pedagogy, 2025)
This qualitative study applies J.L. Austin's Speech Act Theory to analyze Chris Rock’s stand-up comedy show Selective Outrage. It focuses on identifying types of speech acts (locutionary, illocutionary, perlocutionary) and determining which illocutionary acts are most dominant. Data were collected through observation and note-taking, then analyzed using three stages: data reduction, data presentation, and conclusion. The results show that representative speech acts are the most dominant (44%), followed by expressive (35%), declarative (12%), directive (7%), and commissive (2%). This study offers insights into the use of speech acts in stand-up comedy and provides a deeper understanding of Chris Rock’s comedic style and communication strategies.